Investigating English Lexical Borrowing of Registers in Indonesian Online Dictionary (KBBI VI) - Tatu Siti Rohbiah; Muhamad Riqqi Liwaul Hamdi; Lisca Aulia Hanafi (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2026)
The purpose of this research is to classify, describe, and analyze the form and sound changes that occur in English borrowing in Indonesian across various registers found in the KBBI VI online dictionary. This research is a qualitative study aimed at answering how the changes in borrowing words are analyzed within the framework of lexicology. The instruments for this research are researchers, and the data were sourced from the Oxford Advanced Learner's Dictionary and the Indonesian Dictionary (KBBI VI) online version. The data on English borrowings in Indonesian from 86 registers in the KBBI VI online dictionary indicate that researchers identified only 28 registers and 125 words as English borrowings from the United Kingdom. The dominant register for English borrowings is the Chemistry register. Among the 125 processed borrowing words, phonological changes were found, particularly in vowels and consonants. The types of sound changes observed include: (1) Diphthongization, (2) Monophthongization, (3) Assimilation, (4) Lenition, (5) Metathesis, (6) Syncope, (7) Apocope, (8) Prothesis, (9) Epenthesis, (10) Paragoge, and (11) Double Consonant. The dominant type of sound change in English borrowing in Indonesian is monophthongization. This indicates that when Indonesian borrows words from English, it tends to be through substitution or adaptation to match the pronunciation of Indonesian words.